Digital epidemiological surveillance: the role of mobile applications in identifying positive COVID-19 cases - Castillo Vargas, Andrés; Ramírez Estrada, Sebastián (Revista Colombiana de Ciencias Sociales, 2025)
This study examines the use of the earliest mobile applications deployed as a digital epidemiological surveillance strategy for identifying and tracing positive COVID-19 cases. A descriptive case analysis was conducted through the review, evaluation, and critical synthesis of academic and institutional sources. Findings indicate that all applications analyzed began operating in 2020, with most being voluntary. Several countries integrated geolocation (GPS) technology, and data were handled anonymously. Some applications enabled Bluetooth-based contact tracing, employing both centralized and decentralized data-storage architectures. The results show that while these mobile applications stood out for their rapid development, they also generated considerable controversy regarding data governance and privacy. The study concludes that future health-crisis response efforts must incorporate alternative tracking strategies that do not rely exclusively on these types of digital tools.